Some tendencies of sociocultural, economic and politic development of the North Caucasus from the end of 1960s to the beginning of 1980s years - Tamara Aleksandrovna Boulygina (Наука. Инновации. Технологии)
In this article the realization of the general tendencies in development of the USSR in the 1960th – the 1980th years on the example of the North Caucasus is considered and regional, national and local specifics of North Caucasian history of this period comes to light.